Perbandingan Risiko Dan Return Investasi Pada Indeks Lq 45 Dengan Indeks Jakarta Islamic Index (JII): Perbandingan Risiko Dan Return Investasi Pada Indeks Lq 45 Dengan Indeks Jakarta Islamic Index (JII) - Yoyok Prasetyo (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
This study compares the risks and returns between the two indices in the Indonesian Stock Exchange (IDX), namely the LQ 45 Index and the Jakarta Islamic Index (JII). This research period, starting from January 2008 to December 2017. Based on the normality test, the results obtained that the risk data of the LQ 45 Index are normally distributed while the JII Index risk data is not normally distributed. So that a different test used non-parametric statistics, namely the Mann Whitney test. In this study, the results obtained that there is no significant difference in the risk of the LQ 45 index with the JII index. Whereas based on the normality test for LQ 45 Index return data and JII Index return obtained both data are normally distributed and homogeneous. So that the parametric statistics were used by the T test. And the results obtained that the LQ 45 index return also had no significant difference with the JII index. This is due to almost the same constituents / members of these two indices, or the occurrence of a strong slice between the two. Finally, it can be concluded that the risks and returns between the LQ 45 Index and the JII Index have no significant differences.